Dynamic Imaging of T Cell-Parasite Interactions in the Brains of Mice Chronically Infected withToxoplasma gondii - Marie Schaeffer; Seong‐Ji Han; Tatyana Chtanova; Giel G. van Dooren; Paul Herzmark; Ying Chen; Badrinath Roysam; Boris Striepen; Ellen A. Robey (2009)
Abstract The intracellular parasite Toxoplasma gondii can establish persistent infection in the brain of a mammalian host, a standoff that involves the active participation of host CD8 T cells to control infection. CD8 T cells generally protect against intracellular pathogens by local delivery of effector molecules upon recognition of specific pathogen Ags on invaded host cells. However, the interactions between CD8 T cells, T. gondii, and APCs in the brain have not yet been examined. In this study we have used a mouse infection model in conjunction with two-photon microscopy of living brain tissue and confocal microscopy of fixed brain sections to examine the interactions between CD8 T cells, parasites, and APCs from chronically infected mice. We found that Ag-specific CD8 T cells were recruited to the brains of infected mice and persisted there in the presence of ongoing Ag recognition. Cerebral CD8 T cells made transient contacts with granuloma-like structures containing parasites and with individual CD11b+ APCs, including some that did not contain parasites. In contrast, T cells ignored intact Ag-bearing cysts and did not contact astrocytes or neurons, including neurons containing parasites or cysts. Our data represent the first direct observation of the dynamics of T cell-parasite interactions within living tissue and provide a new perspective for understanding immune responses to persistent pathogens in the brain.